An Analysis Of Affective Assessments Of Online Learning Through WhatsApp Group On The Mathematics Students - Nur'aini Muhassanah; Hamidah Suryani Lukman (Hipotenusa : Journal of Mathematical Society, 2021)
This study aims to describe the affective assessment of online learning through WhatsApp Group (WAG) media for mathematics students. This study is a descriptive quantitative study. The subjects of this study were 20 students of the Mathematics Study Program, Nahdlatul Ulama University, Purwokerto who had filled out the research questionnaire. This research was carried out in July – August 2021. The instrument used to obtain data in this study was a questionnaire containing 6 close-ended questiouns related to affective assessment in online learning with a Likert scale format distributed via Google Form to 20 respondents. This study used descriptive statistical methods as the data analysis. The study shows that the affective assessment of online learning through WhatsApp Group (WAG) for mathematics students was good according to the data obtained from the students’ answers in filling out the questionnaires. During the online learning process, students are able to pay attention well, understand the material more easily, get assignments and assessments, interact and discuss the material actively with lecturers and fellow students. In addition, students also remain motivated to learn online even though learning cannot be done face-to-face.